(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
The objective of this research was to make an approach to assertive interpersonal communicative competence in the knowledge society and globalization. It was developed through bibliographic review and analysis, starting from the bases of communication as indispensable for the globalized society, assertive human communication, the elements and dimensions of communication, as well as the communicative competence necessary for the individual to achieve lifelong learning, referring to the educational system. Among the conclusions, it stands out that assertive interpersonal communication allows individuals to create clearer, more precise and critical messages, necessary for negotiation processes, for the creation and transfer of knowledge, requiring an effort from the individual in the development of metacognitive processes.